Karakteristik Sifat Fisika dan Kimia Tanah Berdasarkan Tipe Pengelolaan Lahan pada Hutan Produksi Di Desa Banyu Urip Lombok Tengah: Physical and Chemical Characteristics of Soil Properties Based on the Type of Land Management In The Production Forest In Banyu Urip Village, Central Lombok - Epy Liana; Muhamad Husni Idris; Irwan Mahakam Lesmono Aji (HUTAN TROPIKA, 2022)
This study aimed to investigate the physical and chemical characteristics of the soil based on the type of land management in the production forest in Banyu Urip Village, Central Lombok. Determination of the sampling point is done by employing stratified random sampling. The sampling points were 22, divided into two types of land: forest land (dominated by MPTS plants and woody plants) and agricultural land (dominated by seasonal plants). Soil samples were taken with two depths, namely 0-10 cm and 10-20 cm. Soil samples taken were disturbed and undisturbed soil with variables of physical properties (texture, bulk density, porosity, and color) and soil chemistry (C-organic). The research results on the physical properties of the soil showed that the soil texture in both types of land was dominated by dusty clay. The average porosity value in agricultural land is 49.33%, and forest land is 49.48% (unfavorable category). The average bulk density value in forest land is 1.39 g/cm3 and in agricultural land is 1.35 g/cm^3 (high category). The soil color of the two land types is dominated by dark brown. The average value of C-organic soil is 1.80% in forest land and 1.72% in agricultural land (low category).